Liver trauma - Puente, Sergio; Contreras, Jaime; Medina, Ricardo; Alee, Gonzalo (Cirugía del Uruguay, 1982)
One hundred and twentY five hepatic rauma reated at Posta Central de la Asistencia Pública de Santiago, Chile, during eleven years, are studied. Injuries were clasified as: superficial lacerations, subcapsular hematomes, deep peripheral lacerations and deep cenral facures (ceacking). Their managements are established. Global mortality was 20.8%. Mattress suures had a 16.5% mortality, against a 68% mortality for hepaic resection. Hepatic artery ligaion is an useful procedure in severe liver damage or for an unexperienced surgeon. Rapid transport to an Urgence Hogpital and intesve preoperative care improves he management of severe liver injuries.